Lymphaticovenular Bypass Surgery for Lymphedema Management in Breast Cancer Patients - Chang, D. W. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2012)
Historically, the reported incidence of upper extremity lymphedema in breast cancer survivors who have undergone axillary lymph node dissection has ranged from 9% to 41% 123456 In the past 2 decades, sentinel lymph node biopsy has become popular as a way to minimize the morbidity associated with axillary dissection without compromising the cure rate for breast cancer patients 678. However, even with sentinel node biopsy, the postoperative incidence of upper limb lymphedema in breast cancer patients remains at 4–10% 56910. Lymphedema occasionally emerges immediately after surgery but most often appears after a latent period 11. Obesity, postoperative seroma, and radiation therapy have been reported as major risk factors for upper extremity lymphedema, but the etiology of lymphedema is still not fully understood 12. Common symptoms of upper limb lymphedema are increased volume and weight of the affected limb and increased skin tension. The increased volume of the affected limb not only causes physical impairments in wearing clothes and in dexterity but also affects patients’ emotional and mental status. Surgical management of lymphedema can be broadly categorized into physiologic methods and reductive techniques. Physiologic methods such as flap interposition, lymph node transfers, and lymphatic bypass procedures aim to decrease lymphedema by restoring lymphatic drainage. In contrast, reductive techniques such as direct excision or liposuction aim to remove fibrofatty tissue generated as a consequence of sustained lymphatic fluid stasis. Currently, microsurgical variations of lymphatic bypass, in which excess lymph trapped within the lymphedematous limb is redirected into other lymphatic basins or into the venous circulation, have gained popularity 131415.
Keywords: breast surgery; lymphatics; upper limb; microsurgery